Effect of macroeconomics variables on stock prices in Bursa Malaysia / Muhammad Nadzmi Ramli and Nurul Syawalni Izzatie Musa - Ramli, Muhammad Nadzmi; Musa, Nurul Syawalni Izzatie (Faculty of Business and Management, 2019)
This study examined the impact of selected macroeconomic variables on the performance of Malaysia stock market over the study period from year 1992 to 2017. The selected macroeconomic variables are interest rate, exchange rate, inflation rate, money supply and oil price. This study applied Ordinary Least Square method (OLS) to determine the effect of selective variables on stock market performance by using 100 quarterly data observations. The empirical results suggest that exchange rate and oil price has statistically significant positive effect on Malaysia stock market performance while interest rate and money supply has statistically significant negative effect on Malaysia stock market performance. However, inflation is found out to be insignificant in determining the stock market performance of Malaysia.